IMF Survey, Volume 31, Issue 21. (IMF Survey; IMF Survey ;, 2002)
Tanzanian President Benjamin William Mkapa's remarks on the inauguration of East AFRITAC could not have been clearer or more emphatic. If Africa is to define its own economic destiny, it must strengthen its ability to design and implement sound economic policies. And policy ownership and capacity building are what the new regional technical assistance center, which opened October 24 in Dar es Salaam, is all about.